Rapid wide QRS tachycardia with an unknown cause. Issue 5 (16th April 2022) - Hu, Dalong; Li, Jingxiu
Abstract: One‐to‐one atrioventricular conduction during atrial flutter is one of the most severe life‐threatening arrhythmias and is hemodynamically perilous. Rapid wide QRS tachycardia often not only occurs in patients with ventricular tachycardia but is also found in supraventricular tachycardia/atrial flutter with preexistent QRS prolongation, supraventricular tachycardia/atrial flutter with QRS prolongation caused by an IC antiarrhythmic drug, and supraventricular tachycardia/atrial flutter with preexcitation. Furthermore, atrial flutter with 1:1 AVC via an accessory pathway is an uncommon presentation of Wolff‐Parkinson–White syndrome. We present a case of atrial flutter with 1:1 rapid AVC in the presence of Wolff–Parkinson–White syndrome. Physicians should be familiar with the rapid wide QRS complex ECG pattern associated with AFL with 1:1 AVC via an accessory pathway. Establishing the definitive diagnosis is essential for selecting an appropriate treatment strategy for improving outcomes.